Graphical models for machine learning and digital communication - Frey, Brendan J. (MIT Press, 1998)
Content Description #Includes bibliographical references and index.
"A Bradford book."
Keywords: Machine learning.; Digital communications.; Graph theory.; elektronické knihy; electronic books